Risk factors analysis for early childhood caries - O. M. Davidian (Эндодонтия Today, 2021)
Aim. To study the dominant antenatal and postnatal risk factors for development early childhood caries (12 – 47 months).Materials and methods. In order to study the dental morbidity of the child population aged 1 to 3 years, permanently living in Moscow, an epidemiological examination of 510 children was carried out. To determine the dental status of the subjects, clinical research methods were carried out. To assess antenatal and postnatal risk factors for the development of caries in children aged 1 to 3 years, a questionnaire survey was conducted between parents or legal representatives. The survey participants answered 5 questions that are important for understanding the causes of early tooth decay.Conclusions. With growing up, the prevalence of caries increases. The prevalence of Early Childhood Caries among the boys and the girls aged 12-23 months and 24-35 months depends on the sex of the child. A statistically significant difference in the intensity of caries in different age groups was revealed; the older the age group, the higher the intensity of caries. The risk of caries in children in the group with the pathological course of the mother's pregnancy is higher than in the group with the normal course of pregnancy. A statistically significant relationship was found between the prevalence of caries in children and the age at which toothbrushing began.